1984
DOI: 10.1007/bf00330974
|View full text |Cite
|
Sign up to set email alerts
|

Mercury-resistant plasmids in bacteria from a mercury and antimony deposit area

Abstract: Most bacterial cells (Pseudomonas, Acinetobacter) obtained from the soil at the Khaidarkan mercury and antimony mine (Kirghiz USSR) contain R plasmids with mercury (HgCl2) resistance determinants. The plasmids have a large molecular mass (about 100 MD, though smaller ones also occur), and at least some of them are transmissive. Many of the Hgr bacteria also display an elevated antimony (SbCl3) resistance, though this trait was not shown to be plasmid-dependent. There are practically no Hgr plasmids in bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 10 publications
0
41
0
Order By: Relevance
“…The plasmid pQM17 had a broad host range when mobilized by RP1 (Table 1) as did pKLl (Lomovskaya et af., 1986). This suggests that small non-conjugative plasmids as well as conjugative plasmids (Kelly & Reanney, 1984;Khesin & Karasyova, 1984;Rochelle et al, 1989) might be important in the maintenance and spread of mercury resistance genes in natural bacterial populations. However, pQM17 was probably not abundant in epilithic bacteria because further attempts to isolate plasmids that were able to transform BD413 to mercury resistance were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The plasmid pQM17 had a broad host range when mobilized by RP1 (Table 1) as did pKLl (Lomovskaya et af., 1986). This suggests that small non-conjugative plasmids as well as conjugative plasmids (Kelly & Reanney, 1984;Khesin & Karasyova, 1984;Rochelle et al, 1989) might be important in the maintenance and spread of mercury resistance genes in natural bacterial populations. However, pQM17 was probably not abundant in epilithic bacteria because further attempts to isolate plasmids that were able to transform BD413 to mercury resistance were unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…Most research on transferable resistances in bacteria isolated from natural environments has concentrated on conjugative plasmids (Kelly & Reanney, 1984;Khesin & Karasyova, 1984;Toranzo et al, 1984;Gauthier et al, 1985), but it has been suggested that the most common types of plasmid in bacteria are small (<20 kb) and therefore non-conjugative (Kelly & Reanney, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes are organized into well-characterized mer operons that are usually located on plasmids and transposons (Silver and Waldeerhaug, 1992;Grinsted et al, 1990). Bacteria carrying mer operons are ubiquitous, being present in great numbers in areas with increased mercury concentrations such as mercury mines (Khesin and Karasyova, 1984) or contaminated soils and waters . They are also invariably found in small numbers in pristine environments.…”
Section: Introductionmentioning
confidence: 99%
“…The environmental Hg R strains screened in this study were from the IMG-Hg Reference Collection partly described previously (Khesin & Karasyova, 1984 ;Bogdanova et al, 1988 ;Yurieva et al, 1997 ;Mindlin et al, 2001). The strains characterized in this study are listed in Table 1 ; their identification was performed as described (Khesin & Karasyova, 1984 ;Bogdanova et al, 1988).…”
Section: Methodsmentioning
confidence: 99%